Pengaruh Return, Pelatihan Pasar Modal dan Lingkungan Sosial Terhadap Keputusan Investasi Mahasiswa Di Pasar Modal: (Studi Pada Galeri Investasi Universitas Hindu Indonesia) - Yoni, Ni Kadek; Putra, I Made Endra Lesmana (Hita Akuntansi dan Keuangan, 2025)
Investment is an activity of placing funds in one or more types of assets over a certain period with the hope of obtaining income and/or increasing the value of the investment in the future. This research aims to determine the influence of Return, Capital Market Training and Social Environment on Student Investment Decisions in the Capital Market (Study at the Investment Gallery of the Indonesian Hindu University). The research uses quantitative methods. The population in this research is student who are members of the Indonesian Hindu University Investment Gallery with a total of 311 people. The number of samples in this study was 76 respondents who were determined using the Slovin formula and tested using multiple linear regression analysis techniques. The results of this research indicate that Return has no effect on students' investment decisions in the Capital Market. Capital Market Training has a positive and significant effect on students' investment decisions in the Capital Market. The Social Environment has a positive and significant influence on investment decisions in the Capital Market.